Spreminjanje urbane rabe tal v Ljubljani = Urban land use change in Ljubljana - Marko Krevs (Dela, 2004)
Efforts to improve theknowledge of urban landuse in Ljubljana, and recent problems andperspectives of monitoring the processes of changing of the selectedcategories of urban landuse in city, municipality and urban region arepresented.